Pendampingan Civic Entrepeneurship di Era New Normal melalui Seminar Nasional - Meiwatizal Trihastuti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
The purpose of this activity is an effort made by a formal educational institution (STKIP Pasundan) as a step to prepare citizens with civic entrepreneurial competence. As one of the objects of a change in the paradigm of life in the new normal era, students are the main spear in creating a new mobility of life in accordance with the principles of civic entrepreneurship. This activity is carried out by conducting seminars through a planned procedure, namely the preparation stage by designing strategies and methods for delivering seminars. Then the implementation stage also ends with an in-depth evaluation and analysis in order to provide developments for further activities. The result of this activity is to have an impact on students' creativity and innovation by creating new opportunities in growing their competencies such as being independent, creative, brave, action-oriented, having a number of solutions and being able to create new opportunities.